New species of Eupalaestrus from Argentina (Araneae, Theraphosidae, Theraphosinae) - Ferretti, Nelson Edgardo (2012)
A new species of Eupalaestrus Pocock, 1901 from northern Argentina is described and illustrated. Males and females of Eupalaestrus larae sp. nov. differ from those all other species of the genus by the color with distinct two parallel longitudinal stripes on the femora, patellae, tibiae and one longitudinal stripe reaching half of metatarsi; the presence of a thickened femur and tibia IV; a straight embolus of the male palpal bulb and retrolateral keel pronounced. Specimens were captured in Chaco province, inhabiting unflooded flat grasslands open areas inside forest in transitional Chaco eco-region.